Effect of e-learning methods on Dental education: An observational study - P Mohan Kumar; Sruthima N. V. S. Gottumukkala; K S. V. Ramesh; T Sreenivasa Bharath; Gautami S Penmetsa; C Naresh Kumar (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: The progress in the usage of technology in hardware, software, and cost-effective Internet connectivity enable the availability of science-related information and its usage in all the developing countries. Hence, in this practical world, there should be a need to implement effective and affordable dental education strategies to attain oral health for all in the coming years. OBJECTIVE: The aim of this study is to reduce the need to teach theory-based, on-site classes, e-learning came into existence. E-learning for dental education may alleviate the burden of severe health worker shortages and deliver affordable access to high-quality dental education. METHODOLOGY: Evaluation and assessment methods were done to know the effectiveness of e-learning in dental education by conducting continuing dental education on newer materials and methods, assignments/formative assessments and by open discussions of case descriptions and their treatment modalities through Edmodo app in our dental institute. Effect on knowledge, skills, attitudes, and satisfaction levels of dental students compared to other traditional methods. RESULTS: Dental e-learning has the capacity to develop into a leading-edge to strengthen clinical training skills among dental students by conducting continuing dental education, assignments, formative assessments, case descriptions, and their treatment modalities through e-learning are the best ways to improve quantity and quality in dental education. CONCLUSION: The probable prospective of e-learning could be innovative or revolutionary because this helps in both theoretical-related and clinical-related advancements, and it is possible only with e-learning in developing countries to meet the quality in education.